Pengaruh Relationship Marketing, Perceived Service Quality, Corporate Social Responsibility terhadap Corporate Image (Universitas Negeri Semarang, 2015)
The purpose of this research is to test relationship marketing, perceived service quality, dan corporate social responsibility toward PT Phintraco Securities Branch Office Semarang Company’s Image. The population in this research is 913 customers of Phintraco Securities Branch Office Semarang per December 2014. The act of samples determining used slovin formula, with 91 respondents by using proportional random sampling. There are positive and significant effect on perceived service quality toward company’s image. While relationship marketing, and corporate social responsibility influenced positively but insignificant toward company’s image. This research suggested that the company need to improve the resources quality through training or workshop in order to be more perceptive and better in responding to customers’ needs. Future researchers will add more variables presumably able to improve corporate image.